Pemberdayaan Masyarakat Melalui Pelatihan Aksesoris Berbahan Bonggol Jagung dalam Mengembangkan Usaha Mandiri - Sutisna, Setiati; Sholih, Sholih; Naim, Mochamad (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Semarang, 2020)
This research was conducted to determine the process, results, supporting and inhibiting factors of training in making accessories made from corncobs in developing an independent business in Diparcraft Kedung Halang Bogor. The method used in this study is a descriptive method with a qualitative approach. The results showed that the training process for making accessories made from corncobs in developing independent businesses through the process of problem identification, research objectives, determining the place and time, determining training methods, and implementing 30% theory learning and 70% practice. The results obtained from the training process were declared effective. Supporting factors include the ability of the tutor in implementation that can adapt to the needs of training participants, high motivation of participants in developing self-sufficiency businesses. The existing inhibiting factors are the insufficient facilities used in terms of quantity and quality, lack of training teaching materials, and the lack of tutors which are obstacles to its implementation.